3D printed components of microbial fuel cells: Towards monolithic microbial fuel cell fabrication using additive layer manufacturing. (February 2017) - You, Jiseon; Preen, Richard J.; Bull, Larry; Greenman, John; Ieropoulos, Ioannis
Highlights: 3D printed membranes showed comparable performance with a conventional membrane. 3D printed conductive polymer material was used as an MFC anode for the first time. Seeking low cost, well performing 3D printable materials can now be pursued. A monolithic 3D printed MFC, requiring no assembly will help advance the technology. Abstract: For practical applications of the MFC technology, the design as well as the processes of manufacturing and assembly, should be optimised for the specific target use. Another burgeoning technology, additive manufacturing (3D printing), can contribute significantly to this approach by offering a high degree of design freedom. In this study, we investigated the use of commercially available 3D printable polymer materials as the MFC membrane and anode. The best performing membrane material, Gel-Lay, produced a maximum power of 240 ± 11 μW, which was 1.4-fold higher than the control CEM with PMAX of 177 ± 29 μW. Peak power values of Gel-Lay (133.8–184.6 μW) during fed-batch cycles were also higher than the control (133.4–160.5 μW). In terms of material cost, the tested membranes were slightly higher than the control CEM, primarily due to the small purchased quantity. Finally, the first 3D printable polymer anode, a conductive PLA material, showed significant potential as a low-cost and easy to fabricate MFC anode, producing a stable level of power output, despite poor conductivity and relatively small surface area per unit volume. These results demonstrate the practicality of monolithic MFC fabrication with individually optimised components at relatively low cost.